Congruence in phrasing between music and rhythmic gymnastics routine as perceived by musicians and dancers - Loo, Fung Chiat; Loo, Fung Ying (2015)
Phrasing is an important aspect in both music and choreography, not only for dancing but also in many sports routines such as rhythmic gymnastics, martial arts, synchronized swimming and figure skating. The understanding of phrasing between music and movement provides a clear and meaningful structure to the entire routine. This study aims to look into whether perception of the congruence of phrasing varies if respondents are trained in different disciplines. Fifty-one musicians and fifty-one dancers participated in this experiment and were asked to choose between two videos. One video was taken from an original rhythmic gymnastics routine and the other was modified to enhance the musical phrasing to synchronize with the movement of the gymnast. The result shows that the enhanced video was chosen by the majority of both musicians and dancers regardless of their training. This indicates that the congruence of phrasing between music and movement was identified by both groups of respondents.